Potential targets of natural medicines: preventing lung cancer pre-metastatic niche formation by regulating exosomes - Zhu, Xiao-yu; Li, Jie (Frontiers in Oncology, 2023)
Lung cancer is one of the most devastating diseases worldwide with high incidence and mortality, and the incidence continues to rise. Metastasis is the leading cause of death in lung cancer patients, yet the molecular effectors underlying tumor dissemination remain poorly defined. Research findings in recent years confirmed primed microenvironment of future metastatic sites, called the pre‐metastatic niche, is a prerequisite for overt metastasis. Exosomes have recently emerged as important players in pre‐metastatic niche formation. Natural medicines have traditionally been rich sources of drug discovery. Some of them exhibit favorable anti-lung cancer activity. The review focused on the latest advances in the regulation of the pre‐metastatic niche formation in lung cancer by the contents of exosomes of representative natural medicines. Additionally, the mechanism of natural medicines was summarized in detail, which would provide new insights for anti-cancer new drug development.